Analysis and Reconstruction of Laboratory Activity Design Digestive System Material - Saragi, Foniman; Supriatno, Bambang; Purwianingsih, Widi (Bioilmi: Jurnal Pendidikan, 2025)
Digestive system material is an essential part of the biology curriculum for Grade XI senior high school. Eventhough the material is critical, many existing LADs fail to facilitate the transformation of students' factual knowledge into conceptual understanding, which limits the development of higher-order thinking skills and scientific reasoning. Therefore, this study is conducted to to analyse and reconstruct Laboratory Activity Design (LAD) on digestive system material in grade XI senior high school to improve the effectiveness of practicum-based learning. The research method used is descriptive with the ANCORB approach (Analyse, Test, Reconstruct, and Create LAD). LAD analysis was conducted using a Vee Diagram developed by Novak and Gowin, including focus questions, objects or events, concepts and theories, data recording and transformation, and knowledge claims. The analysis showed that the initial LAD had several weaknesses, such as unclear focus questions, lack of object identification, and limited concepts. Based on these findings, LAD was reconstructed to be more structured, focusing on the link between theory and practice. The reconstruction results are expected to improve students' conceptual understanding and facilitate the process of scientific knowledge construction effectively in learning the digestive system.